2014
DOI: 10.1002/2013ja019305
|View full text |Cite
|
Sign up to set email alerts
|

On the presence and properties of cold ions near Earth's equatorial magnetosphere

Abstract: Plasma flows related to magnetospheric convection or ULF waves often increase cold ions' kinetic energy sufficiently above the spacecraft potential energy so that these ions can be detected by charged particle instrumentation. Other detection methods also reveal the presence of cold ions even in the absence of flows. By applying such methods to complementary data sets obtained from particle, electric field, and magnetic field measurements by the multiple Time History of Events and Macroscale Interactions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 75 publications
8
108
1
Order By: Relevance
“…These parameters in Table 1 are consistent with the particle data of THEMIS observation and those reported by Lee and Angelopoulos [2014]. The time evolution of the emission is controlled mostly by the nonlinear growth rate and optimum amplitude, which are determined by the density and average perpendicular velocity of energetic protons [Omura et al, 2010, equation (54); Shoji and Omura, 2013, equation (22)].…”
Section: Comparison With the Nonlinear Growth Theorysupporting
confidence: 84%
“…These parameters in Table 1 are consistent with the particle data of THEMIS observation and those reported by Lee and Angelopoulos [2014]. The time evolution of the emission is controlled mostly by the nonlinear growth rate and optimum amplitude, which are determined by the density and average perpendicular velocity of energetic protons [Omura et al, 2010, equation (54); Shoji and Omura, 2013, equation (22)].…”
Section: Comparison With the Nonlinear Growth Theorysupporting
confidence: 84%
“…Plumes are usually found in the afternoon and last for days, but weaken in density, width and flux with time (Chandler et al 1999, Borovsky and Denton 2008, Darrouzet et al 2008, Moore et al 2008, Spasojevic and Sandel 2010. Low-energy ions are found just inside the magnetopause, not only in plasmaspheric plumes (Matsui et al 1999, André and Lemaire 2006, Lee and Angelopoulos 2014, and indications of a cold 'plasmaspheric wind' have been found (Dandouras 2013). However, as for the high latitude case, observations of low-energy ions onboard a sunlit, and charged spacecraft have been rare.…”
Section: Ions In Near-earth Spacementioning
confidence: 99%
“…Nightside equatorial cold ions were sampled using the ULF wave technique by Lee and Angelopoulos (2014) out to ∼13 R E during predominantly quiet times (observation interval between 2008 and 2013). They used the THEMIS satellites to sample cold ions during intervals of enhanced bulk plasma flows (convection or ULF waves) that accelerated ambient cold ions above the spacecraft potential so they could be detected by the particle instruments carried by the three inner THEMIS spacecraft (low inclination, 1.5 by 13 R E ).…”
Section: Ionospheric Plasma Transportmentioning
confidence: 99%
“…These nightside equatorial observations support the interpretation by Engwall et al (2009b) that the outflowing LEP observed with Cluster II were likely energized above the energy needed to form a wake at locations near the plasma sheet. Lee and Angelopoulos (2014) used the heavy ion density ratios and higher temperatures on the nightside to also infer a major ionospheric source of LEP at L < 13 R E . They noticed another trend: the median temperatures of all three species were quite warm (10-100s eV) and traced out a path from pre-midnight through the dawn side, consistent with particles in the warm plasma cloak, with evidence of another path of the nightside warm ions along the dusk side.…”
Section: Ionospheric Plasma Transportmentioning
confidence: 99%
See 1 more Smart Citation